INTERNATIONAL SECURITY BASED ON THE UNITED STATES RESPONSE POST TO THE SOUTH CHINA SEA CLAIM BY THE PEOPLE’S REPUBLIC OF CHINA - Muhammad Budiana; Yusa Djuyandi (Universitas Padjadjaran, 2023)
Conflicts and tensions in the South China Sea are getting bigger after the People’s Republic of China claimed control over the Spratly and Paracel Islands and the waters that intersect with most of the countries in Southeast Asia. China’s efforts to place military forces on the two islands and the intensification of their ship patrols in the waters of the South China Sea indicate that China wants to strengthen its claims and hegemony, although of course these claims immediately receive a response from countries whose borders intersect in the South China Sea, mainly ASEAN member countries. This research used a descriptive qualitative research method. The source of the data for this research consists of secondary data which is gained from reports or media coverage that examine security issues in the South China Sea. Various data that have been obtained are then checked for validity through data validation techniques, where this technique carried out through triangulation of data or sources. As a superpower, the United States does not remain silent but participates in balancing security for countries that feel they are being claimed. Because what China has done is considered to have the potential to limit the rights and freedoms of the international community in using the waters in the South China Sea as their trade access, the United States and its allies who are members of AUKUS (Australia, United Kingdom, and the United States) are indeed pushing for the principle of freedom of navigation. On this basis, the United States took steps to address the problems and tensions in the South China Sea. The legal umbrella used by the United States is the same as that used by ASEAN countries, namely based on the 1982 United Nations Convention on the International Law of the Sea (UNCLOS 1982).